Fenomena Penundaan Mandi Wajib Pasca Haid pada Mahasiswi UIN Alauddin Makassar: Perspektif Hukum Islam - Nasir, Herlina; Aisyah, Siti; Sastrawati , Nila (Universitas Islam Negeri Alauddin Makassar, 2023)
Mandatory bathing is a must for women who experience menstruation (menstruation). However, most menstruating women delay taking a mandatory bath. The main problem in this study is the phenomenon of postponement of compulsory postmenstrual bathing for women in the perspective of Islamic law, a case study of female students comparing madhab and law UIN Alauddin Makassar. The purpose of this study is to determine the perspective of Islamic law regarding the phenomenon of postponement of compulsory post-menstrual bathing for women among female students comparing mazhab and the law of UIN Alauddin Makassar. The method used in this study is field research which is descriptive analytic. The data analysis method uses qualitative description. Data management techniques obtained from the field, to take data management techniques are carried out by reducing data, presenting data, and drawing conclusions. The results of this study found that the factors of the delay in mandatory bathing that they had done were due to lazy mandatory bathing, forgetting, being sick, wanting to make sure whether their menstruation had stopped or not, and other factors vaginal discharge. Some of them have postponed their mandatory bath by 1 day and some even postponed it for up to 4 days. According to the view of Islamic law, if the reason is to convince, it is permissible as long as it does not exceed 1 day. But if it exceeds more than 1 day, then it is included as deliberate neglect of its obligations. But if the reason is forgetting or lazy to take a bath then this is not justified because it includes neglect and will get sin.